Respons Pertumbuhan dan Hasil Mentimun (Cucumis sativus L.) pada Kombinasi Media Substrat dengan Sistem Hidroponik: Growth and Yield Response of Cucumber (Cucumis sativus L.) in Several Combinations of Substrate Medium with Hydroponic System - Aini, Nurul; Muzakiyah, Efi Zulfita (Jurnal Hortikultura Indonesia, 2023)
The characteristics of the soiless media are an important factor in cultivating cucumber plants using a hydroponic substrate system. The aim of this research is to study the effect of a combination of media derived from oyster mushroom baglog waste, husks and husk charcoal on the growth and yield of cucumbers in a hydroponic substrate system. The experiment was structured based on a Randomized Complete Block Design (RCBD) with 3 replications. The treatment consisted of 9 media combinations, namely mushroom baglog waste (100%), rice husks (100%), charcoal husks (100%), and combinations with each ratio of 25:75; 50:50 and 75: 25%. The results of the research showed that cucumbers grown in a combination of mushroom baglog waste media + husk charcoal (25:75) produced higher leaf area, number of leaves, dry weight, root volume as well as weight and number of fruit compared to 100% mushroom baglog waste media. These results are supported by improvements in the physical properties of the media (porosity, air space), absorption and nutrient content in the media. In conclusion, to be an ideal medium, mushroom baglog waste should be combined with husk charcoal in a ratio of 25:75. Key words: Baglog waste, nutrient, porosity, root volume